The influence of nutrition and various materials on tomato cultivation in hydroponics - Abdiev Zafarali; Khurramov Ulugbek; Karimov Jamshid; Zokirov Kurbonalijon; Omonov Mamatqobil; Jumanov Laziz; Ruzmetov Ghulam (E3S Web of Conferences, 2023)
The article presents the results of the research conducted in order to prepare small hydroponics models, trays, hydroponics materials, (gravel, sand, coconut, prilite) drip irrigation and collector equipment, preparation of basic solutions with the participation of various macro and micro fertilizers and their composition. In the determination, indicators of rN, ES, t ºC of the basic solution were constantly studied. Also, the mixing ratio of each basic solution with water (1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1: 9, 1:10) is analyzed. The irrigation and fertilizing tank in the small model hydroponics system has a capacity of 10-20 l, a solution of mineral fertilizers dissolved in water is placed in it, and the solution of fertilizers in it is dripped through the opening and closing valves to the irrigation pipes and mixed with water to the plants. The concentration and consumption of the mineral fertilizer solution was controlled using an electroconductometer device on the water falling from the droppers, and the solution falling from the droppers at the top, middle and lower part of the dropper pipes was determined using measuring cylinders (1 l).